Exploring implicit and explicit crossmodal colour-flavour correspondences in product packaging - Piqueras-Fiszman, B; Velasco, C; Spence, C (2012)
We report a study designed to investigate consumers' crossmodal associations between the colour of product packaging and flavour varieties in crisps (potato chips) among Colombian and British consumers, using two methods. In a modified version of the Implicit Association Test (IAT), the stimuli consisted of green and blue coloured packets and the flavours normally paired with these colours for a certain brand in the UK and Colombia. In an explicit word (colour) association task, unbranded, grayscale packets with three new flavours were shown instead. The results obtained from both tasks revealed two main kinds of associations between the colour of the packaging and flavour types: (1) A learned association through a conventional pairing attributable to a specific brand, and (2) an association between a flavour and its potential packaging colour, based on the colour of the primary named ingredients. In addition, when comparing associative patterns documented in the two countries, no specific cultural differences were found. The techniques used here and the results reported are relevant for RandD since they contribute to the existing knowledge on colour associations and raise questions regarding their origin. © 2012 Elsevier Ltd.